EFFECT OF FLAT AND HEMISPHERICALLY ENDED CYLINDER BIRD MODEL WITH FINITE ELEMENT MODELLING OF BIRD STRIKE - Yuniarti, Endah; Sitompul, Sahril Afandi (Indonesian Journal of Aerospace, 2019)
This research studies influence of bird model on impact pressures during bird strike, namely Hugoniot and Stagnation pressure through initial modelling by numerical simulations using finite element method. Finite element simulation of bird strike have primarily modelled the bird as either a flat or hemispherically ended cylinder. The geometry is simulated with different L/D ratio, 1.4, 1.6, 1.8 and 2.0. Elastic-plastic hydrodynamic material model is used in simulation. Bird model simulation are using lagrangian method and initial velocities are 100, 200 and 300 m/s. Simulation results of hemispherically ended cylinder bird models show variation of L/D ratio provide Hugoniot pressure 10-19 times higher than stagnation pressure in L/D = 1.4, 8-18 times in L/D = 1.6, 9-17 times in L/D = 1.8 and 4-16 times in L/D = 2. The Hugoniot pressure shows a lower value at an L/D ratio of 1.6 compared to other ratios and the Stagnation pressure is higher at L/D ratio 2. As for cylindrical bird model show variation of L/D ratio provide Hugoniot pressure 35-38 times higher than stagnation pressure in L/D = 1.4, 30-47 times in L/D = 1.6, 31-52 times in L/D = 1.8 and 28-48 times in L/D = 2. The Hugoniot pressure shows a lower value at an L/D ratio of 1.4 and 1.6 compared to other ratios and the Stagnation pressure is higher at L/D ratio 2.